Efficient production of glycyrrhetinic acid in metabolically engineered Saccharomyces cerevisiae via an integrated strategy - Wang, Caixia (Microb Cell Fact, 2019)
BACKGROUND: Glycyrrhetinic acid (GA) is the most important ingredient in licorice due to its outstanding anti-inflammatory activity and wide application in the medicine and cosmetics industries. Contemporary industrial production of GA by acid hydrolysis of glycyrrhizin which was extracted from Glycyrrhiza plants, is not environment-friendly and devastates farmland since the Glycyrrhiza rhizomes grow up to 10 m underground. RESULTS: In this study, GA was produced through metabolically engineering Saccharomyces cerevisiae by introducing the entire heterogeneous biosynthetic pathway of GA. Codon optimized CYP88D6 and CYP72A154, combined with β-AS (β-amyrin synthase encoding gene) and the NADPH-cytochrome P450 reductase gene of Arabidopsis thaliana were introduced into S. cerevisiae. The resulting strain (Y1) produced 2.5 mg/L of β-amyrin and 14 μg/L of GA. The cytochrome b5 from G. uralensis (GuCYB5) was identified and the introduction of this novel GuCYB5 increased the efficiency of GA production by eightfold. The joint utilization of the GuCYB5 gene along with 10 known MVA pathway genes from S. cerevisiae were overexpressed in a stable chromosome integration to achieve higher GA production. Using the combined strategy, GA concentration improved by 40-fold during batch fermentation. The production was further improved to 8.78 mg/L in fed-batch fermentation, which was increased by a factor of nearly 630. CONCLUSIONS: This study first investigated the influence of carbon flux in the upstream module and the introduction of a newly identified GuCYB5 on GA production. The newly identified GuCYB5 was highly effective in improving GA production. An integrated strategy including enzyme discovery, pathway optimization, and fusion protein construction was provided in improving GA production, achieving a 630 fold increase in GA production. The metabolically engineered yeast cell factories provide an alternative approach to glycyrrhetinic acid production, replacing the traditional method of plant extraction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-019-1138-5) contains supplementary material, which is available to authorized users.